Hybrid Working: Challenges and Opportunities in Managing Employee Performance in the Age of Flexible Working - Effiyaldi Effiyaldi; Setyowati Subroto; Maulid Sakaria (Oikonomia : Journal of Management Economics and Accounting, 2025)
The hybrid work model has become a new paradigm in the modern workplace, offering flexibility for employees while challenging organizations in managing performance. The main challenges in this system include the difficulty of measuring productivity, proximity bias, ineffective communication, and limited direct supervision. This study aims to explore optimal strategies for managing employee performance in a hybrid work environment. Using a qualitative approach through a case study method, this study involved in-depth interviews with managers, hybrid employees, and HR teams from organizations that have implemented a flexible work system. Thematic analysis was used to identify key patterns in performance management. The results showed that a results-based assessment system, the use of AI-based performance monitoring technology, and inclusive communication are key to success in the hybrid model. In addition, trust-based leadership and continuous feedback are needed to create a productive and fair work environment. With the right strategy, organizations can optimize productivity, increase employee engagement, and create a balance between flexibility and work effectiveness. This study provides insights for organizations in designing adaptive policies to support the sustainability of the hybrid work model in the future.